Crystal keepers [compact disc, unabridged] - Mull, Brandon, 1974- (Mull, Brandon, 1974- Five Kingdoms, 2015)
Cole Randolph ventures to a new kingdom as he continues his search for his friends and also pursues his quest to mend what has gone awry with the magic in the Outskirts. Can he overcome the challenges ahead, or will he be stranded forever in a world between reality and imagination?